2022
DOI: 10.1097/cce.0000000000000636
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Major Adverse Kidney Events in Extracorporeal Membrane Oxygenation Survivors

Abstract: The majority of extracorporeal membrane oxygenation patients develop acute kidney injury, and 40-60% require renal replacement therapy. This study aimed to examine determinants of major adverse kidney events in extracorporeal membrane oxygenation survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A study conducted by Bobba A et al showed that major adverse kidney events (MAKE) could affect the reversibility of AKI and could increase the mortality. 22 …”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Bobba A et al showed that major adverse kidney events (MAKE) could affect the reversibility of AKI and could increase the mortality. 22 …”
Section: Discussionmentioning
confidence: 99%
“…A study in VA-ECMO patients demonstrated 11% dialysis dependence (median follow-up 64 months in non-ESKD patients) and 51% prevalence of CKD at 1 year [ 29 ]. Another recent study of predominantly VA-ECMO survivors (80%) reported major adverse kidney events (median follow-up time 3.4 years) which include AKI, partial/no recovery at discharge, and RRT on the same date or after ECMO initiation [ 30 ]. In two studies of exclusively VV-ECMO patients, no and 6.8% patients were dialysis dependent at hospital discharge, but longer-term renal function was not reported [ 11 , 31 ].…”
Section: Discussionmentioning
confidence: 99%